Cyanotoxin Response Leads to Successful Resilience Planning. Issue 3 (7th April 2021) - Johnson, Christopher; Davis, Jason; Sherman, Timothy
Abstract : Although Salem, Ore., had a well‐designed monitoring and treatment process in place, an algal bloom with historic consequences led the city to implement immediate mitigation measures and establish a long‐term strategy for meeting future water quality challenges.